种染料敏化太阳能电池FeSe/Fe对电极的制备方法 (2018)
本发明公开了种染料敏化太阳能电池FeSe/Fe对电极的步水热制备方法，其步骤如下：将铁片用碱和酸分别进行处理，以除去表面油污和氧化物，并清洗干净，然后成定角度置于带有聚四氟乙烯内衬的不锈钢反应釜中；另外，将摩尔浓度为0.21mol/L~4.2mol/L的水合肼和摩尔浓度为0.01mol/L~0.8mol/L的硒粉溶入去离子水中，充分混合后转移到该反应釜中，在120℃~200℃、2~18h的条件下反应完全，取出试样，洗涤并真空干燥即为对电极。本发明公开的FeSe对电极的制备方法简单、廉价，制备周期短，可进行快速大规模的制备。 The invention discloses a one-step hydrothermal manufacturing method of a dye sensitization solar cell FeSe2/Fe counter electrode. The method comprises the following steps that an iron sheet is processed by alkali and acid so as to remove a surface oil contaminant and oxide, the iron sheet is cleaned and then is placed in a stainless steel reaction vessel with a polytetrafluoroethylene lining at a certain angle; besides, hydrazine hydrate with a 0.21mol/L-4.2mol/L molar concentration and a selenium powder with 0.01mol/L -0.8mol/L molar concentration are dissolved in deionized water and are fully mixed, and then a mixture is transferred to the reaction vessel; at 120DEG C-200DEG C and for 2-18 hs, complete reaction is performed, a sample is taken out